A study on vocabulary acquisition among students : a case study of grade six (6) students of international modern Arabic school in Malaysia - Mehzabeen, Auliar Najiihah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Due to the importance of understanding the process of vocabulary acquisition, this study attempts to understand the important element in learning English as a second language. A detailed research was conducted on two methods of learning which are the acquisition of receptive and productive vocabulary. This study looks at the effectiveness of each method in teaching by devising series of tests on Grade Six students of the International Modern Arabic School in Putrajaya, Malaysia. A sentence completion task and essay writing were utilised to determine the acquisition of vocabulary among students. Through detailed analysis, this study concludes that there is a positive correlation between students' improvement on the acquisition of receptive and productive vocabulary. Moreover, it is identified that the majority of the students improved in their vocabulary knowledge towards the end of the semester. Although receptive learning helps in vocabulary acquisition, the most effective method of language acquisition was via productive vocabulary acquisition. The study is relevant in the field of education, particularly for students of foreign language.